Green synthesis of silver nanoparticles through oil: Promoting full-thickness cutaneous wound healing in methicillin-resistant Staphylococcus aureus infections - Wang, Yuhan; Li, Qinmei; Peng, Xiaomin; Li, Zheng; Xiang, Jun; Chen, Yunru; Hao, Kaiyuan; Wang, Shuaiyang; Nie, Dongyang; Cui, Yao; Lv, Feifei; Wang, Ying; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Due to the emergence of multi-drug resistant microorganisms, the development and discovery of alternative eco-friendly antimicrobial agents has become a top priority. In this study, a simple, novel and valid green method was developed to synthesize Litsea cubeba essential oil-silver nanoparticles (Lceo-AgNPs) using Lceo as a reducing and capping agent. The maximum UV absorbance of Lceo-AgNPs was appeared at 423 nm and the size was 5-15 nm through TEM result. The results of FTIR and DLS showed Lceo provided sufficient chemical bonds for Lceo-AgNPs to reinforce its stability and dispersion. The in vitro antibacterial effects of Lceo-AgNPs against microbial susceptible multidrug-resistant Escherichia coli (E. coli) and Methicillin-resistant Staphylococcus aureus (MRSA) were determined. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of Lceo-AgNPs against E. coli were 25 μg/mL and 50 μg/mL. The MIC and MBC of Lceo-AgNPs against MRSA were50 μg/mL and 100 μg/mL, respectively. The result of Scanning electron microscopy (SEM) showed that the amounts of bacteria obviously decreased and the bacteria cells were destroyed by Lceo-AgNPs. In vivo research disclosed significant wound healing and re-epithelialization effects in the Lceo-AgNPs group compared with the self-healing group and the healing activity was better than the sulfadiazine silver group. In this experiment, Lceo-AgNPs has been shown to have effects on killing multidrug-resistant bacteria and promoting wound healing. This study suggested Lceo-AgNPs as an excellent wound newtype drug for treatment of wounds infected by multidrug-resistant bacteria, and now expects to proceed with clinical research.